2008
DOI: 10.1161/circulationaha.107.747642
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Compared With Intravenous Bolus Abciximab Application in Patients With ST-Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: Background-Abciximab reduces major adverse cardiac events in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention (PCI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
140
2
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(147 citation statements)
references
References 45 publications
2
140
2
3
Order By: Relevance
“…40 An abbreviated infusion of GPIs (<12 hours) may be beneficial in the ACS setting. Intracoronary GPIs might also maximize efficacy, 41 but these approaches would need to be prospectively tested in ACS patients.…”
Section: Discussionmentioning
confidence: 99%
“…40 An abbreviated infusion of GPIs (<12 hours) may be beneficial in the ACS setting. Intracoronary GPIs might also maximize efficacy, 41 but these approaches would need to be prospectively tested in ACS patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 The application of platelet glycoprotein IIb/IIIa receptor antagonists (in combination with antiplatelet agents, anticoagulants and anti-inflammatory drugs) can decrease infarct size, reduce the degree of microvascular damage and improve myocardial perfusion. 8 Research has shown that, with a severe thrombus burden, application of thrombus aspiration and tirofiban during an emergency PCI procedure can improve blood no/ slow reflow and lead to improved outcomes. 9 There remains, however, a substantial thrombus load in patients with acute MI who have exceeded the emergency PCI time window (12 h).…”
Section: Introductionmentioning
confidence: 99%
“…This could probably be explained by myocardial stunning which took some time to resolve. Further, in an magnetic resonance imaging (MRI) study, Thiele and colleagues found no significant improvement in LVEF and volumes 1 to 4 days after an acute STEMI [6]. Thus, our first echocardiogram performed within 3 days after a STEMI appears representative of LV function post-MI.…”
Section: Discussionmentioning
confidence: 64%
“…It may improve clinical outcomes in patients with STEMI undergoing primary PCI. This alternative approach has been investigated in several studies to further characterize the clinical benefits of this mode of drug delivery, but the results are still controversial [6][7][8][9][10]. Ischemic injury after MI affects not only systolic but also diastolic function of the left ventricle (LV).…”
Section: Introductionmentioning
confidence: 99%